Hypothetical Learning Trajectory for Seventh Graders' Understanding of Square through Techno-Ethno-Realistic Mathematics Education - Farida Nursyahidah; Maya Rini Rubowo; Arif Wibisono; Khoiriya Latifah; Windia Hadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
The concept of squares is a fundamental topic in junior high school geometry, serving as a foundation for understanding quadrilaterals and more advanced geometric concepts. However, many seventh-grade students struggle to learn the material. distinguishing the properties of squares from other quadrilaterals and often rely on procedural understanding rather than conceptual reasoning. To address this challenge, this study aims to develop a Hypothetical Learning Trajectory (HLT) for seventh-grade students' understanding of squares through Techno-Ethno-Realistic Mathematics Education (TE-RME). This study uses a design research methodology consisting of three stages: preliminary design, teaching experiments, and retrospective analysis. This study involved seventh-grade students at a junior high school in Semarang. The focus of this article is on the initial design stage, namely the development of a hypothetical learning trajectory that includes four main activities: (1) observing the context video; (2) finding the perimeter of a square using rods and GeoGebra; (3) finding the area of ​​a square using rods, origami paper, and GeoGebra. The series of activities in this learning path is designed to help students build a deeper understanding of the square concept, while fostering an appreciation of local culture and diversity in mathematical thinking. This hypothetical learning trajectory is designed to be implemented in an experimental classroom and research-based teaching using TE-RME.